2011
DOI: 10.1016/j.electacta.2011.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten oxide in polymer electrolyte fuel cell electrodes—A thin-film model electrode study

Abstract: a b s t r a c tThin films of WO x and Pt on WO x were evaporated onto the microporous layer of a gas diffusion layer (GDL) and served as model electrodes in the polymer electrolyte fuel cell (PEFC) as well as in liquid electrolyte measurements. In order to study the effects of introducing WO x in PEFC electrodes, precise amounts of WO x (films ranging from 0 to 40 nm) with or without a top layer of Pt (3 nm) were prepared. The structure of the thin-film model electrodes was characterized by scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…demonstrated that Ti, W, Sn, Nb, Ta, and Sb are stable as oxides, hydroxides or metals under fuel‐cell‐relevant conditions, that is, at a potential of 1.0 V (vs. SHE), pH 0, and T =80 °C, using thermochemical calculations. Experimentally, most of the work in the recent years has been devoted to the development of conductive oxides based on titanium dioxide,8588 tungsten oxide,88, 89 tin oxide;88, 90 zirconium oxide or tantalum oxide 88. Significant progress has been made in the improvement of the electronic conductivity of different oxide materials by doping them with a metallic element or by modifying the oxide surface 91.…”
Section: Oxide‐based Support Materialsmentioning
confidence: 99%
“…demonstrated that Ti, W, Sn, Nb, Ta, and Sb are stable as oxides, hydroxides or metals under fuel‐cell‐relevant conditions, that is, at a potential of 1.0 V (vs. SHE), pH 0, and T =80 °C, using thermochemical calculations. Experimentally, most of the work in the recent years has been devoted to the development of conductive oxides based on titanium dioxide,8588 tungsten oxide,88, 89 tin oxide;88, 90 zirconium oxide or tantalum oxide 88. Significant progress has been made in the improvement of the electronic conductivity of different oxide materials by doping them with a metallic element or by modifying the oxide surface 91.…”
Section: Oxide‐based Support Materialsmentioning
confidence: 99%
“…ions towards the precursor nanofibers should be less affected by the electrostatic repelling in the case of positive potential, leading to the higher reaction rate for the positive potential than the negative potential. Figure 5a and b shows the CV curves of the samples prepared at different potentials in 0.5 M H 2 SO 4 solution, which exhibit the characteristic shape reported for tungsten oxide [4,8,[31][32][33]. These CV curves exhibit a sharp cathodic peak at the end of the negative scan and a wide anodic peak in the positive scan except for the sample obtained at -0.15 V. These two peaks can be ascribed to the reduction of the hydrogen ions and oxidation of the hydrogen inserted into the WO 3 Á2H 2 O structure [8,[31][32][33], respectively.…”
Section: Resultsmentioning
confidence: 88%
“…Both curves exhibit a sharp cathodic peak in the negative scan and a wide anodic peak in the positive scan. These two peaks are caused by the hydrogen intercalation and de-intercalation into/out of the WO 3 structure or hydrogen reduction and oxidation [16,18,47], respectively. In the cathodic process, the H ?…”
Section: Resultsmentioning
confidence: 97%
“…For example, nitrogen doped carbon [7][8][9][10][11], tungsten carbide [12], and transition metal chalcogenides [13] have been found to have electrocatalytic activity for oxygen reduction reaction and transition metal carbides and oxides such as CoMoC [14], WC [15], and tungsten oxide especially WO 3 [16] exhibit electrocatalytic activity for fuel molecular oxidation. Tungsten oxide has been extensively investigated as supports of Pt or active materials in the form of mixture with Pt, which generally shows enhanced electrocatalytic activity than Pt itself mainly due to the hydrogen spill-over effect and resistance to CO-poisoning [17,18]. A recent report has manifested that WO 3 in itself possesses electrocatalytic activity for hydrogen oxidation [16], displaying a high promise in application as the anode catalysts of fuel cells.…”
Section: Introductionmentioning
confidence: 99%